Broadband and high efficiency metal multi-layer dielectric grating based on non-quarter-wave coatings as a reflective mirror - 张文飞 孔伟金 云茂金 刘均海 孙欣 (Chinese physics B, 2012)
This article deals with designing a broadband and high efficiency metal multi-layer dielectric grating （MMDG） used to compress and stretch an ultrashort laser pulse. The diffraction characteristics of the IVIMDG are analysed by using the rigorous coupled-wave method. The multi-layer dielectric used as the reflective mirror is made up of non- quarter-wave coatings. Taking the diffraction efficiency of the -1 order as the value of merit function, the parameters such as groove depth, residual thickness, duty cycle, and reflective mirror are optimized to obtain broadband and high diffraction efficiency. The optimized MMDG shows an ultra-broadband working spectrum with the average efficiency exceeding 97% over 160 nm wavelength centred at 1053 nm and TE polarization. The optimized MMDG should be useful for chirped pulse amplification.